Bioprospecting of Lentinus squarrosulus Mont., an underutilized wild edible mushroom, as a potential source of functional ingredients: A review. (March 2017) - Lau, Beng Fye; Abdullah, Noorlidah
Abstract: Background: Lentinus squarrosulus Mont. is a wild edible mushroom appreciated by the local communities in Africa and Asia for its taste and meaty texture as well as its purported medicinal benefits; however, it is relatively unknown to the communities in other parts of the world and it remains underutilized thus far. In view of the increasing scientific studies carried on L. squarrosulus, a systematic compilation of the research progress and future prospects is deemed timely. Scope and approach: This review summarized the widely scattered literature on L. squarrosulus with an emphasis on its nutritional and nutraceutical properties. Cultivation techniques for the production of basidiocarp, mycelium, and culture broth – representing the different stages in its life cycle and sources of distinct chemical components – are also presented. Key findings and conclusions: Basidiocarps of L. squarrosulus are good sources of carbohydrate, protein, and minerals, and are considered to be on par with other edible-medicinal mushrooms. Bioactive chemical components, such as phenolic compounds, flavonoids, immunostimulatory glucans, antifungal proteins, and lectins, have been identified and/or isolated from L. squarrosulus . Apart from various in vitro bioactivities assessment, the extracts of L. squarrosulus were noted to confer protection against oxidative stress and enhanced the healing of ulcer in animal models. Large-scale production of L. squarrosulus is deemed feasible considering the widely occurrence of this species and growing reports on its successful artificial cultivation via solid-substrate and liquid fermentation. In conclusion, findings thus far indicate that the basidiocarp and mycelium could be developed as potential sources of functional ingredients but further studies, particularly on bioactive compounds, mechanism of action in vivo leading to clinical trials, and quality control of L. squarrosulus biomass from different cultivation methods, are recommended. Graphical abstract: Highlights: Lentinus squarrosulus is traditionally eaten by Asian and African communities. Bioactive secondary metabolites, polysaccharides, and proteins were isolated. Extracts and isolated compounds demonstrated various biological activities. Basidiocarp, mycelium, and culture broth are potential sources of functional ingredients. Lentinus squarrouslus biomass merits consideration for commercialization.